Katalán tanulságok a Kárpát-medence számára - Szilágyi, István (Közép-Európai Közlemények, 2012)
The 21st century is the age of globalisation, of connections between cultures and civilisations representing different values and value systems. The Westfalian international system based on the principle of the exclusivity and omnipotence of state entities has been transformed and has largely disappeared. The notion of the Nation State, which dates back to the 18th and 19th centuries and conveys the concept of homogenity, has also lost its validity. At the end of the 20th century the processes aiming at democracy and principle of subsidiarity had a significant influence on the state structure in the three semi-peripherical areas of the word. The transformation in the Spanish state-system calls attention to its importance. Between 1979 and 1983, in the first phase of the institutional development of the democratic parliamentary monarchy which displaced the Franco system, Spain saw the realisation of a democratically regulated coexistence between the state (the Kingdom of Spain), historical nations possessing their own language (Basque, Galician, Catalan, Valencian), and regions without a history (Cantabria, Asturiass, Extremadura, Madrid, Murcia, La Rioja etc.). In Spain the population is made up of 20% Catalans, 6% Basques, 2,5% Galicians,and 2,5% Valencians. It is a fact that by creating an autonomy model resting on cooperation between seventeen self-governing communities, the Spanish new democracy has played an exemplary role in the solution of a centuries-old ethno-regional problem. The system formed between 1979 and 1983 has proved to be viable to the present day. The relative stability of a democratic state structure in the historical sense does not preclude change. The institutional system is in a process of constant motion. Changes pointing from the semi-federalism of autonomous communities to federalism, which are based on national and cultural identities, have markedly accelerated from the second half of the 1990s. In July 2006, they led to the passing of the new Autonomy Statute of Catalonia. The separation of the autonomous province, which has gained independent nation status and the formation of an independent state with the capital of Barcelona has presented itself as a realistic alternative. At the same time, current events and processes in Spain provide important lessons for the autonomy aspirations of national minorities in the Carpathian basin. The Spanish-Catalan solution involving the notion of the concept of the cultural nation may bring official attention to the issue of the validity and feasibility of this model in the case of the minorities in the multinational states of our region. The reality of political self-government, territorial autonomy, the preservation of identity and its connection to the official use of language as well as the creation and maintenance of the necessary institutional framework calls attention to the practicability of a democratic state-formation practice already existing in the European Union.